To solve the polynomial subtraction (2x^2 + 6x + 1) - (3x^2 + 3x + 9), we first need to distribute the negative sign across the second polynomial.
So, we start with:
(2x^2 + 6x + 1) - (3x^2 + 3x + 9) = 2x^2 + 6x + 1 - 3x^2 - 3x - 9
Now, we combine like terms:
-
Combine the \( x^2 \) terms: \( 2x^2 - 3x^2 = -1x^2 \) or \(-x^2\)
-
Combine the \( x \) terms: \( 6x - 3x = 3x \)
-
Combine the constant terms: \( 1 - 9 = -8 \)
Now, putting it all together, we get:
\(-x^2 + 3x - 8\)
Thus, the correct answer is:
D) (2x^2 + 6x + 1) - (3x^2 + 3x + 9) = -x^2 + 3x - 8.